Discrepancу (sublimation) and deviation of the personality formation process in distance education conditions - Садықова, Бағила; Есназарова, Ұлжалғас; Тоқбергенова, Айгүл (Pedagogy and Psychology, 2022)
Despite the successful and active delivery of video lessons and online sources during distance education, the time and conditions showed some flaws in the distance education system (DES) of Kazakhstan’s educational system. These two years of using the DES at Secondary and Higher institutions enabled us to define the advantages and disadvantages of this type of teaching; revealed the possible trajectories of making some advancements and improvements in this sphere. The benefits and drawbacks of distance learning were analyzed thoroughly in the works of many authors in the course of pandemics. Those works gave rational justifications that distant education was the only alternative to traditional education in situations of emergency. In this article, we will consider the psycho-pedagogical aspects of DES, based on the previous works of the authors. Because the role of physiological and physiologic processes is often neglected in the DES. Distance education requires pedagogues of schools and universities to take into account the psychological characteristics of their students, to create comfortable conditions to acquire the materials of the lessons. It is essential to indicate that without sensory perception the effects processes–assimilating and accommodating knowledge will be lower. Along with this, pedagogues of secondary and high educational institutions must be educated in psychology, as students might encounter certain difficulties which lead to psychological disorders because of the number of tasks. Teachers must know how to identify both positive and negative types of deviation. In the case of positive deviation, the teacher’s main duty is to detect it on time, and to support and reinforce. On the other hand, if the deviation is negative, they must carefully analyze the causes of the problem. However, how these processes can be executed during distance learning? Are there any possible solutions to overcome the obstacles in inconveniencies of remote teaching? This article will be devoted to finding the answers to these questions by doing research work, for determining the effects of responsibility and high interests of students on levels of discrepancy in the teaching process. Key words: Distance education; deviation; discrepancy (sublimation); personality development; education; pedagogy; psychology.